Benefits and Challenges of Implementing Social Emotional Learning (SEL) in Education: A Systematic Literature Review - Desma Astia Lavenda; Khalimah Azizah Nur; Efendi Nasori (Universitas Muhammadiyah Ponorogo, 2025)
This study investigates two research questions: (1) What are the benefits of implementing Social Emotional Learning (SEL) in educational settings? and (2) What challenges are faced in implementing SEL within educational contexts? A systematic literature review was conducted by analyzing peer-reviewed articles published between 2019 and 2024 across databases such as Google Scholar, ERIC, ScienceDirect, and Garuda. The research design follows Tóth et al. (2023), applying the PICOC criteria (Population, Intervention, Comparator, Outcome, Context) and thematic analysis from international and Indonesian journals. Addressing the first research question, four key benefits of SEL emerged: (1) enhanced self-awareness and emotional regulation among Generation Z; (2) improved communication and intercultural collaboration in language learning; (3) academic gains through increased motivation, engagement, and critical thinking; and (4) promotion of equity through inclusive environments. In response to the second question, five significant challenges were identified: (1) limited teacher competence in SEL; (2) misaligned curriculum and assessment systems; (3) cultural and contextual barriers; (4) digital adaptation issues among Generation Z; and (5) rigid policies emphasizing narrow academic metrics. This review provides valuable insights for educators, policymakers, and researchers to support effective SEL integration in educational contexts by offering a balanced synthesis of advantages and obstacles.